Hydrolysis of Peptide Bonds in Protein Micelles Promoted by a Zirconium(IV)‐Substituted Polyoxometalate as an Artificial Protease. Issue 49 (13th August 2020) - Quanten, Thomas; Savić, Nada D.; Parac‐Vogt, Tatjana N.
Abstract: The development of artificial proteases is challenging, but important for many applications in modern proteomics and biotechnology. The hydrolysis of hydrophobic or unstructured proteins is particularly difficult due to their poor solubility, which often requires the presence of surfactants. Herein, it is shown that a zirconium(IV)‐substituted Keggin polyoxometalate (POM), (Et2 NH2 )10 [Zr(α‐PW11 O39 )2 ] (1 ), is able to selectively hydrolyze β‐casein, which is an intrinsically unstructured protein at pH 7.4 and 60 °C. Four surfactants (sodium dodecyl sulfate (SDS), N ‐dodecyl‐ N, N ‐dimethyl‐3‐ammonio‐1‐propanesulfonate (ZW3‐12), 3‐[(3‐cholamidopropyl)dimethylammonio]‐1‐propanesulfonate (CHAPS), and polyethylene glycol tert ‐octylphenyl ether (TX‐100)), which differ in the nature of their polar groups, were investigated for their role in influencing the selectivity and efficiency of protein hydrolysis. Under experimental conditions, β‐casein forms micellar structures in which the hydrophilic part of the protein is water accessible and able to interact with 1 . Identical fragmentation patterns of β‐casein in the presence of 1 were observed through SDS poly(acrylamide) gel electrophoresis both in the presence and absence of surfactants, but the rate of hydrolysis varied, depending on the nature of surfactant. Whereas TX‐100 surfactant, which has a neutral polar head, caused only a slight decrease in the hydrolysis rate, stronger inhibition was observed in the presence surfactants with charges in their polar heads (CHAPS, ZW3‐12, SDS). These results were consistent with those of tryptophan fluorescencequenching studies, which showed that the binding between β‐casein and 1 decreased with increasing repulsion between the POM and the polar heads of the surfactants. In all cases, the micellar structure of β‐casein was not significantly affected by the presence of POM or surfactants, as indicated by circular dichroism spectroscopy. Abstract : Surf and snip : The development of artificial proteases is challenging, but important for many applications in modern proteomics and biotechnology. The ability of a Zr IV ‐substituted Keggin polyoxometalate ([Zr(α‐PW11 O39 )2 ] 10− ) to promote the hydrolysis of the amphipathic protein β‐casein, which forms micelles in aqueous solution, is demonstrated in the absence and in the presence of different surfactants.